The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.15253/2175-6783.2015000600010
|View full text |Cite
|
Sign up to set email alerts
|

Maternal assessment of pain in premature infants

Abstract: Objective: to identify mothers' perceptions about the pain in their premature babies in the Neonatal Intensive Care Unit. Methods: evaluative, quantitative study with investigative nature conducted with 19 mothers of hospitalized premature newborns. Data were obtained from closed questions, answered by mothers. Results: from the participants, two (10.5%) reported that newborns are unable to feel pain. From the 17 mothers who said that premature babies can feel pain, the majority (94.1%) identified crying as a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…It is up to the health professional to brief the parents about the signs of pain, especially the mothers who most often experience the hospitalization of their children. Besides the briefing, these mothers should be invited to participate in care to be able to call the team at the first sign of discomfort or stress of their NB 23 .…”
Section: Discussionmentioning
confidence: 99%
“…It is up to the health professional to brief the parents about the signs of pain, especially the mothers who most often experience the hospitalization of their children. Besides the briefing, these mothers should be invited to participate in care to be able to call the team at the first sign of discomfort or stress of their NB 23 .…”
Section: Discussionmentioning
confidence: 99%
“…Parents can play an active role in both assessment and management of neonatal pain ( 6 ). Parents who are able to be present with their infant at the hospital can identify signs of pain and discomfort ( 7 9 ). However, parents may underestimate their infant's pain, compared to the assessment of health care professionals ( 10 , 11 ).…”
Section: Reviewmentioning
confidence: 99%
“…A study on the father's participation in the children's hospitalization showed that although the role of primary caregiver is that of the mother, the parents showed involvement and an active attitude. 23 The Kangaroo Method is responsible for the integration between father, mother and newborn. It favors the bond and the sense of competence to take care of the children.…”
Section: Attitudes Towards Pain: I Take Care Of Itmentioning
confidence: 99%